A Practical Framework and Model for Promoting Cost-Inclusive Evaluations - Nadini Persaud (Journal of MultiDisciplinary Evaluation)
Background: Cost studies are an important component of any serious professional evaluation. Regardless of whether an evaluation is conducted in the public or private sector, decision-makers want answers to two fundamental questions: (1) Is the program, project, or investment worthwhile? and (2) Can funds be used in a better way? The answers to both questions rely on the use of cost analysis techniques. However, according to the literature, most evaluations do not include any type of cost study (see Christie & Fleischer, 2010) and when studies are included, very few are of high quality and rigor (see Madsen, Eddleston, Hansen, & Konradsen, 2017). This may in part be as a result of the relatively limited emphasis placed on this important topic in the evaluation-specific literature, coupled with the reality that many evaluators lack expertise to conduct cost analysis studies.